1999
DOI: 10.1097/00007435-199904000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Stability Study on Specimens Mailed to a State Laboratory and Tested With the Gen-Probe PACE 2 Assay for Chlamydia

Abstract: Mailed specimens were exposed to longer transport times and elevated temperatures; despite this, 99% of the results using courier specimens agreed with the mailed specimen results. Eighty-eight women tested positive and 891 women tested negative for chlamydia on both specimens. When the 11 specimens with discrepant results were retested by polymerase chain reaction, 10 were positive for chlamydia, with 9 concurring with the mailed specimen results. Results of specimens in this study were not adversely affected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…This is supported by studies describing the effects of storage and shipping conditions on test outcome for Chlamydia spp. 2,11 Although temperature variation en route was not assessed for either shipping method in the present study, it seems reasonable to assume that couriered samples experienced less variation in temperature and less extreme temperatures and for shorter times than did postal samples. Although the highest temperature measured at the time of unpacking a sample sent by USPS in this study was 24uC, maximum ambient temperatures at the shipping and receipt cities were 47uC and 41uC, respectively.…”
mentioning
confidence: 76%
“…This is supported by studies describing the effects of storage and shipping conditions on test outcome for Chlamydia spp. 2,11 Although temperature variation en route was not assessed for either shipping method in the present study, it seems reasonable to assume that couriered samples experienced less variation in temperature and less extreme temperatures and for shorter times than did postal samples. Although the highest temperature measured at the time of unpacking a sample sent by USPS in this study was 24uC, maximum ambient temperatures at the shipping and receipt cities were 47uC and 41uC, respectively.…”
mentioning
confidence: 76%
“…Recent studies have shown that specimens are not adversely affected by heat and extended transit times. 10 The DH has an approximate turnaround time of ten days. In cases with a positive result, the DH staff contact our ED quality assurance coordinator by fax or telephone, who confirms by chart review that the patient received appropriate antibiotic therapy.…”
Section: Methodsmentioning
confidence: 99%
“…As a result, there has been a shift to centralized or consolidated laboratory services that has occurred on both a regional and a national scale (7). Although the issue of transit times for clinical specimens to reach a central laboratory has become much more important, there have been very few investigations of the impact of delays (6). Bacteria that are particularly sensitive to ambient conditions include Shigella spp., Neisseria gonorrhoeae, Neisseria meningitidis, S. pneumoniae, H. influenzae, and anaerobes (9).…”
Section: Streptococcus Pneumoniae Haemophilus Influenzae Andmentioning
confidence: 99%